Application of low field and solid-state NMR spectroscopy to study the liquid/liquid interface in porous space of clay minerals and shales - Borysenko, Artem; Clennell, Ben; Burgar, Iko; Dewhurst, David; Sedev, Rossen; Ralston, John (Diffusion Fundamentals, 2009)
In petroleum research understanding displacement, redistribution, and adsorption of oil and water plays an important role. To study complex multi-component systems such as liquid/liquid/mineral interactions in the porous space of clays and shales we applied low field (2 – 15 MHz) and high resolution (300 MHz) NMR spectroscopy. The detailed NMR analysis shows that the results from low field NMR measurements are in good correlation with the solid-state data. Consequently the process of liquid/liquid displacement can be characterised by considering the relaxation times, signal amplitudes and chemical shifts together.